On the Anthropocene formalization and the proposal by the Anthropocene Working Group - C. Soriano (Geologica Acta, 2020)
In the coming years the Anthropocene will be likely submitted to formalization by the Anthropocene Working Group as a chronostratigraphic unit of the Geologic Time Scale. This has generated an increasing debate among detractors and defenders of its formalization in general, and of the proposal by the Anthropocene Working Group in particular. Here, the main issues regarding the Geologic Time Scale and the rules to formalize units, the empirical data supporting the Anthropocene formalization and the critiques to formalize it are critically reviewed. The procedure to formalize the Anthropocene is not dissimilar from those of the other units of the Geologic Time Scale and has been essentially based on stratigraphic and geologic criteria. Following the recommendation of the Anthropocene Working Group and based on the empirical evidence on the Anthropocene as it is expressed in strata and, more important, on the immanent and structural link between the Anthropocene and the reproduction of capital, it is proposed to define Capitalian as a Stage of the Anthropocene Epoch. In this way, a truly comprehensive understanding of the Earth history is obtained, which comprises the ultimate causes of the ongoing planetary transformation and its stratatigraphic expression.